THE ANALYSIS OF INCOME OF BROILER CHICKEN FARMERS PARTNERSHIP PATTERN AT AL-AN'AM FARM - Effendi, Subhan; Ahmad, Ilham; Saleh, Muhammad (ITScience (Information Technology and Science), 2023)
This study aims to analyse the income of broiler chicken farmers partnership patterns at Al-An'am Farm. This research was conducted between June and July 2022, at Attangsalo Village, Ma'rang District, Pangkep Regency. This descriptive study aims at describing the research variables to find out the pattern and income of broiler chicken farming businesses in collaboration with companies at Attangsalo Village Ma'rang Subdistrict, Pangkep Regency. The population in this study was one person who partnered with a company. The data analysis used descriptive statistics, exploring at partnership patterns, operational costs, revenues, and income. The results show that the patterns of collaboration with a company is written agreement without security deposit. The income of farmers who partner with companies tend to be higher.